KETERAMPILAN SUPERVISOR DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SMKN 2 PELAIHARI - Adi Saputra, Riski; Murhartoyo; Sakka, Ambo; Metroyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The quality of learning in Vocational High Schools (SMK) still faces various challenges, particularly related to teachers’ pedagogical competence and the effectiveness of the learning process. One strategic effort to improve learning quality is through effective academic supervision. However, in practice, the implementation of supervision is often not optimal due to the limited skills of supervisors. This study aims to describe supervisors’ skills, analyze the implementation of academic supervision, and explain the role of supervisors’ skills in improving learning quality at SMKN 2 Pelaihari. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and then analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The results show that supervisors’ skills, including technical, interpersonal, and conceptual aspects, play an important role in the implementation of academic supervision. Communication, observation, and evaluation skills are the dominant factors in enhancing supervision effectiveness. The supervision process is carried out through planning, classroom observation, and follow-up stages, using collaborative and coaching-based approaches. These approaches are proven to enhance teachers’ reflective awareness and encourage improvements in learning quality, although there are still limitations in the follow-up stage. Therefore, strengthening supervisors’ skills and implementing sustainable supervision are key factors in improving learning quality in vocational schools.